Performance limits of terahertz zero biased rectifying detectors for direct detection - Golenkov, A.G.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Performance limits of uncooled unbiased field effect transistors (FETs) and Schottky-barrier diodes (SBDs) as direct detection rectifying terahertz (THz) detectors operating in the broadband regime have been considered in this paper. Some basic extrinsic parasitics and detector-antenna impedance matching were taken into account. It has been concluded that, in dependence on radiation frequency, detector and antenna parameters, the ultimate optical responsivity (ℜopt) and optical noise equivalent power (NEPopt) of FETs in the broadband detection regime can achieve ℜopt ~ 23 kV/W and NEPopt ~ 1⋅10⁻¹² W/Hz¹/², respectively. At low radiation frequency ν in the THz spectral region the NEPopt of SBD detectors can be better by a factor of ~1.75 as compared to that of Si MOSFETs (metal oxide semiconductor FETs) and GaAlN/GaN HFETs (heterojunction FETs) with comparable device impedances.